Pengetahuan dan Paparan Informasi Berhubungan dengan Keikutsertaan Wanita Pasangan Usia Subur (PUS) dalam Skrining Inspeksi Visual Asam Asetat (IVA) di Puskesmas Harapan Raya Pekanbaru - Fatiyani Alyensi; Zuchrah Hasan; Okta Vitriani (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2018)
Cervical cancer is a disease characterized by abnormal cell growth and development in the cervix of a woman. Cervical cancer is the number two cause of death in the world. This study aimed to determine the proportion of women of reproductive age couples who performed IVA screening and factors related to the behavior of women reproductive age couples in IVA screening. The research was conducted at Harapan Raya Pekanbaru Health Center. The type of research used is an analytical cross sectional study. Subjects were women at reproductive age couples as many as 400 people, with married inclusion criteria of at least 3 years, the independent variables studied were knowledge, education, information exposure,fatalismcancer, family history of cancer, and employment. Data analysis is done by multiple logistic regression. The proportion of women of reproductive age couples who did IVA screening was 55.2%. Low-level women of reproductive age couples with low knowledge were 2.4 times at risk (95% CI = 1.33 - 3.14) not screening cervical cancer compared with EFA women with high knowledge. PUS women not exposed to information at risk of 2.9 (95% CI = 1.60 - 5.25) did not screen for cervical cancer. Knowledge and information exposure are related to the behavior of women at reproductive age couples in cervical cancer screening. It is recommended to Puskesmas to conduct counseling and cervical cancer screening counseling for women at reproductive age couples